Freqüências de irrigação para Eucalyptus grandis e Pinus elliottii em viveiro - Freitag, Ângela Simone (2007)
This study had as object to evaluate the irrigation management influences in Pinus elliottii Engelm. and Eucalyptus grandis W. Hill ex Maiden. seedlings, according to its deficiencies, keeping the germination and development qualities. The statistical design was a bifactorial in randomized blocks, with time subdivided blocks and three repetitions. As main plot were characterized the frequencies of four irrigation (treatments), being: T1 (one irrigation per day); T2 (two irrigations per day); T3 (three irrigations per day) and T4 (four irrigations per day) and, as subplot in time, eight evaluation periods for pinus and seven for eucalyptus. The data were weekly collected, obtaining the height and the number of remaining seedlings for both species, as well as the number of leaves in each seedling for eucalyptus. The amount of water used in both treatments, during each irrigation, was 5 litters per minute. Based on the results, it was possible to assert that, for both species, low irrigation frequencies gave bad results due to quality and quantity of seedlings during the evaluation period. For pinus, the indicated frequency was four irrigations per day, while for eucalyptus the indicated frequency was three per day